Being children again: art, play, and memory in interdisciplinary creation (The Voz a Vos Bulletin, 2025)
This article presents a reflection on the importance of interdisciplinarity in contemporary art, based on the creative process of the work "Jugando a ser hormigas" (Playing at Being Ants), a performance that articulates dance, music, and theater. It considers how the integration of different disciplines enables a horizontal dialogue between artistic languages, fostering collective creative processes that challenge the artist not only from a technical perspective, but also from a sensitive, symbolic, and vital perspective; an introspective encounter. The work, conceived as a tribute to the teacher, researcher, and artist Abelardo Jaimes, becomes an act of healing and a reconnection with the essence of the creative act: play, exploration, and constant questioning.
Keywords: interdisciplinarity; collective creation; game; art pedagogy; memory